Differences in the response of Sprague-Dawley and Lewis rats to bezafibrate: the hypolipidemic effect and the induction of peroxisomal enzymes - Pill, Johannes; Völkl, Alfred; Hartig, Franz; Fahimi, H. Dariush (Archives of toxicology, 1992)
The effects of bezafibrate administered at 10 and 50 mg/kg/day for 7 days to male Sprague-Dawley (SD) and Lewis rats were investigated in order to determine the interrelation between the changes in serum and hepatic lipid contents and activities of selected peroxisomal, microsomal and mitochondrial enzymes in the two rat strains. In both strains, bezafibrate effectively reduced serum and hepatic lipids, increased the liver weight, induced a proliferation of peroxisomes, and selectively elevated the activities of carnitine acetyltransferase and of the enzymes of the peroxisomal Β-oxidation system. Moreover, immunoblotting revealed that the drug specifically enhanced the concentration of only those peroxisomal enzymes involved in fatty acid Β-oxidation. The data obtained demonstrate that although the responses initiated by bezafibrate are qualitatively similar in both strains, they differ in their magnitude in a dose-dependent manner, with the Lewis strain exhibiting a more pronounced response than the SD rats. These results show that dose-dependent strain differences as well as the generally known species differences should be taken into account in pharmacological and toxicological evaluations of fibrates in rodents. Furthermore, generalization and extrapolation from rodent studies should be treated with great caution.